Proposed new interior design of LKIM headquarters at Lot 354, Jalan Ampang, 50450 Kuala Lumpur for Lembaga Kemajuan Ikan Malaysia (LKIM) / Muhamad Amirudin Ahmad Bakir - Ahmad Bakir, Muhamad Amirudin (Faculty of Architecture, Planning and Surveying, 2012)
In order to accomplish the final stage of learning process, a final year student pursuing a diploma course in Interior Design is requisite to organize a project. The project that had been chosen is to 'Propose a New Interior Design of LKIM Headquarters at Lot 354, Jalan Ampang, 50450 Kuala Lumpur for Lembaga Kemajuan Ikan Malaysia (LKIM)’. This headquarters is one of the compensation for the client as a way to establish their scope of managing all activities about fisheries in Malaysia since LKIM already exists and getting well known by Malaysians. According to the objectives and the issues, a space planning must be suitable with the design concept and images. The realization of the design is difficult as there are procedures that have to be followed. The planning and the ideas that are to be applied into the space must be linked to the concept and images. The good design is produced with the concept and the images, which is put into the design axis and followed by the development of ideas. All the design must be connected to the project that has been decided. Before making the design, one of the major aspects that must be considered is to get the information. In research, the case study of design schematic and the planning have to be done to make sure that client give good impression and reaction to our design. Last but not least, every work must be organized well starting from the design development until the end of the project.